The Arab G.D.P. per capita under the synthetic control method - MOHAMED, Ahmed (KDI School, 2021)
This paper will revolve around testing how would the Arab region be in terms of G.D.P. per capita if the Greater Arab Free Trade Area would have never gone into force in 2005, which the country members adopted in its General Provisions and negotiation rounds. A comparison between synthetic and actual status of G.D.P. per capita levels will be then analyzed to test if the synthetic obtained data would have been more beneficial (G.D.P. per capita) for all country members. The synthetic model is developed with control data based on North America, the European Union (E.U.), South Asia and East Asia as the biggest blocs and trade partners of the Arab region to generate G.D.P. per capita synthetic data of the Arab region, compared later with the actual data. The focus of the study will be from 1985 till 2019. Therefore, the main findings show the G.D.P. per capita after 2005 of the Arab region is much higher on real data than on the synthetic data that accords to the agreement''s scenario, never going into force. The difference between synthetic and actual data reaches a peak of 100% in 2008.
Thesis(Master) -- KDI School: Master of Public Policy, 2021
Keywords: Free trade--Arab countries; National income--Arab countries